Norway : Selected Issues. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper examines the role of the State Petroleum Fund in Norwegian economic policy, as a means to promote a sustainable long-term fiscal position and to help maintain the competitiveness of the non-oil ('mainland') economy in the face of high oil export revenues. The paper documents the historical development of the wage bargaining framework in Norway, a country with a fairly centralized framework. It also compares recent wage developments in Norway with those of its trading partners to assess the implications for Norway's international competitiveness.